The extract of Ophiocephalus striatus affect levels of TNF-α, TGF-β1, IL-17 and suPAR, pulmonary diffusing capacity for carbon monoxide, and health-related quality of life in stable COPD patients with muscle wasting - Susanthy Djajalaksana; Nunuk S. Muktiati; Teguh R. Sartono; Vitri Iriani; Ratih Renata; Sasongko Adhi; Harun A. Rasyid (Russian Open Medical Journal)
Objective — This study aimed to evaluate the effect of Ophiocephalus striatus extract on body composition, levels of TNF-α, TGF-β1, IL-17, suPAR and neutrophils, diffusing capacity of the lungs for carbon monoxide (DLCO) and health-related quality of life (HRQoL) in stable COPD patients with muscle wasting. Methods — Clinical pre- and post- quasi-experimental study of 32 stable COPD patients with muscle wasting from the Pulmonary Outpatient Clinic of Saiful Anwar General Hospital Malang, determined in accordance with the Global Initiative for Chronic Obstructive Lung Disease (GOLD) 2016 and bioelectrical impedance analysis (BIA) measurements (FFM <14.6 kg/m; BMI <18.5 kg/m2). Measurements of the following health-related parameters for the QoL due to COPD were performed before and after the nutritional intervention of 3,000 mg of O. striatus extract daily for 12 weeks: TNF-α, TGF-β1, IL-17 and suPAR levels (by ELISA), neutrophils (by blood test), DLCO (by body plethysmography), and CAT score. Results — A non-significant reduction of TNF-α (p=0.302), IL-17 (p=0.275), neutrophil (p=0.619), and suPAR (p=0.674) levels, along with an increase in DLCO (p=0.369), occurred after 12 weeks of O. striatus extract administration. However, the level of TGF-β1 declined significantly (p=0.022), followed by an increase in QoL as assessed by the CAT score (p=0.000). There was no significant correlation between inflammatory cytokines and DLCO, nor with the CAT score. Conclusion — The study results demonstrated a potential role of oral nutritional supplementation in the management of COPD patients with muscle wasting.